Human Risk in Agriculture - Sheytanov, Pavel (Research Papers, 2020)
The risk related to human resources is one of the five most important risks in agriculture. Taking precautions and using the instruments for managing the human risk the right way would increase the sustainability of the farm. This paper examines the importance of human risk and the actions that the Bulgarian farmers are taking to manage it. It also studies the relation between the workforce and farmers’ attitude towards risk.